Quantification study of temperature distribution based on time series similarity in lithium titanate oxide anode based pouch battery. (July 2022) - Liu, Zehui; Wang, Chu; Miao, Chen; Guo, Xinming; Gao, Yinghui; Zhang, Xiaohu; Sun, Xianzhong; Sun, Yaohong; Yan, Ping
Abstract: Lithium titanate oxide (LTO) anode based lithium-ion battery has a large instantaneous output power and obvious uneven surface temperature distribution happens when discharging under ultrahigh discharge rates. To better know about the thermal characteristics, the thermal performance analysis of a 15 Ah LTO anode based pouch battery during the discharge is carried out under the discharge rates from 1C to 40C. In this work, the definition of different temperature zone is proposed, and four evaluation parameters are introduced to evaluate the temperature distribution from aspects of the temperature fluctuation, the aggregation degree, the time series similarity during the discharge process, and the distribution similarity under different discharge rates. Moreover, the strategy of the cooling device design is proposed. The results reveal the temperature distribution mode of the battery during the discharge. The similarity during each discharge rate is high. The battery has a fixed and aggregated high temperature zone at 10C and above, the medium temperature zone and low temperature zone moves outwards during the discharge, while the periphery of the battery is always in low temperature zone. Besides, the similarity between the adjacent discharge rates is high. In conclusion, this work reveals the temperature distribution mode of the battery and can instruct the specific cooling device design for the battery. Highlights: The temperature distribution mode of LTO anode based battery under ultrahigh discharge rates has been studied. A time series similarity method is introduced first in the evaluation of the temperature distribution. A fixed high temperature zone exists under discharge rate 10C and above. The similarity between adjacent discharge rates is high.